Evaluasi Keberhasilan Reklamasi Lahan Bekas Tambang Pasir (Galian C) dengan Tanaman Gamal (Gliricidia sepium (Jacq.) Steud) (Studi Kasus di Desa Cibeurem Wetan, Cimalaka, Sumedang, Jawa Barat) - Ikrar Nusantara Putra; Dhea Rakhmat Ginanjar; Apong Sandrawati (Fakultas Pertanian Universitas Padjadjaran, 2014)
Cimalaka is well known for its high quality sands for building material. Unfortunately, the sand mines opened in Cimalaka areas are less managed and have degraded. Usually, the soil has no organic horizon so that no vegetation covered the soils. The land was mined repeatedly without appropriate reclamation effort, thus supported the invasive plants species to cover the site. Gliricidia sepium has known as invasived plants. This research was conducted to evaluate ecosystem function of post-sand mining land Cimalaka, Sumedang, West Java that revegetation with Gliricidia sepium. The research showed that Gliricidia sepium was high potentially improved soil quality in eks sands mining. The roots of Gliricidia sepium increase the content of organic in soils, so that with the litters. The enhancement of organic content potentially impacted increasing organism activities that would impact to soil quality improvement. Soils quality improvement showed by increasing soil pH and organics contents into more suitable for organism growth.